AGAMA MENURUT TEORI SEKULARISASI PETER BERGER DAN JOSE CASANOVA DAN RELEVANSINYA TERHADAP PENANGANAN TERORISME - Natalio Kawarnidi (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study aims to analyze the role of religion within the framework of secularization theory developed by Peter Berger and Jose Casanova, as well as to examine its relevance to the phenomenon of terrorism in contemporary society. This research uses a qualitative approach with a literature study method. The main sources of the study include Berger's works The Sacred Canopy and The Desecularization of the World, as well as Casanova's Public Religions in the Modern World, supported by secondary literature related to religion, radicalism, and terrorism. The analysis is conducted critically and comparatively to observe the interaction between secularization, religious revival, and the emergence of extremist movements. The results of the study indicate that secularization does not eliminate religion but rather transforms its role in the public sphere. Religious revival can strengthen moral and social solidarity, but it also has the potential to produce exclusive and radical religious expressions that legitimize violence. Therefore, efforts to counter terrorism need to consider the dynamics of religion and secularization, not solely relying on security approaches.